Yellow moving van - Koertge, Ronald (Pitt poetry series., 2018)
Ron Koertge's Yellow Moving Van is a collection of relaxed and buoyant and sometimes very funny poems that address Desi & Lucy with the same courtesy as Walt Whitman. The author celebrates his roots in the Mid-West and a few pages later stops off in Transylvania. These poems like to sometimes embrace and sometimes confound expectations, and they all stand together as enemies of the murky and pompous. There is apparently no subject -- Prometheus, a fifty foot woman, or Death himself -- that is unwilling to fall under his spell.